A Discourse Analysis of Volunteer Recruitment Appeals in English - Nguyễn Minh Trường (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims to identify and describe the discourse features of Volunteer Recruitment Appeals in English. The results of research may help Vietnamese learners of English get an insight into the distinctive characteristics of VRAs.